Democratic transitions and monetary policy: are democratic central banks different?. (1st October 2020) - Bjørnskov, Christian; Rode, Martin
Abstract : Empirical studies have shown democracies to be more supportive of pro-market institutions than authoritarian regimes; however, to date, it is virtually unknown through which channel democracy might actually create institutional improvements. In addition, causality between democracy and economic institutions is anything but clear, as competing hypotheses highlight. In this article, we examine the possible association of democratisation and political instability with sound monetary policy and the independence of central banks, both of which can be considered central pillars of an economic policy aimed at producing overall prosperity. Results mainly indicate that stable transitions to democracy are followed by strongly improved access to sound money and more independent central banks, probably because stable shifts to electoral democracy create incentives for policymakers to refrain from using monetary policy for short-run gains. Conversely, we also find evidence that especially unstable democratic transitions could impede the establishment of a more independent central bank, making inflationary policies and high money growth more likely.